Frequency of KCNQ1 variants causing loss of methylation of Imprinting Centre 2 in Beckwith-Wiedemann syndrome - Eßinger, Carla; Karch, Stephanie; Moog, Ute; Fekete, György; Lengyel, Anna; Pinti, Eva; Eggermann, Thomas; Begemann, Matthias (Clinical epigenetics, 2020)
Beckwith-Wiedemann syndrome (BWS) is an imprinting disorder caused by disturbances of the chromosomal region 11p15.5. The most frequent molecular finding in BWS is loss of methylation (LOM) of the Imprinting Centre 2 (IC2) region on the maternal allele, which is localised in intron 10 of the KCNQ1 gene. In rare cases, LOM of IC2 has been reported in families with KCNQ1 germline variants which additionally cause long-QT syndrome (LQTS). Thus, a functional link between disrupted KCNQ1 transcripts and altered IC2 methylation has been suggested, resulting in the co-occurrence of LQTS and BWS in case of maternal inheritance. Whereas these cases were identified by chance or in patients with abnormal electrocardiograms, a systematic screen for KCNQ1 variants in IC2 LOM carriers has not yet been performed.